THE IMPLEMENTATION OF A PROBLEM SOLVING MODEL USING HIGHER ORDER THINKING SKILLS QUESTIONS TO DEVELOP VOCATIONAL HIGH SCHOOL STUDENTS' CRITICAL THINKING SKILLS - Febriani, Syifa; Eryanto, Henry; Nida, Ria Rahma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study describes the implementation of a problem-solving model through Higher Order Thinking Skills (HOTS) questions to develop students' critical thinking skills in the Public Relations and Protocol Management subject at SMK Negeri 48 Jakarta. It covers the planning and implementation of learning, the quality of the developed HOTS instrument, and the emergence patterns of Facione's six critical thinking indicators, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation, among students with different critical thinking levels. The study employed a qualitative descriptive approach with a case study design. The unit of analysis comprised 34 eleventh-grade students of the Office Management and Business Services program, with six students and two teachers selected as interview informants through purposive sampling. Data were collected through classroom observation, in-depth interviews, a HOTS case-study test based on a Gala Dinner crisis scenario, and instrument testing using Pearson Product Moment correlation and Cronbach's Alpha. Data analysis was conducted through data reduction, data display, and conclusion drawing, combined with a Thinking Process Matrix Rubric to categorize students into High, Moderate, and Low critical thinking groups, validated through source triangulation. The HOTS instrument was valid for 10 of 15 items, with r values ranging from 0.389 to 0.610, and reliable with a Cronbach's Alpha of 0.636. Polya's problem-solving model was implemented systematically through four phases and elicited all six critical thinking indicators across all student categories, though with varying quality: the High category demonstrated mature and comprehensive abilities, the Moderate category tended to be normative, while the Low category remained very limited. The study recommends sustained application of a single-case HOTS-based problem-solving model with more intensive scaffolding for low-ability students, and the development of similar assessment instruments for other vocational subjects.